Legal study of the granting of spousal consent in the transfer of land rights from joint property due to unregistered marriage - Aprilyani Aprilyani; Soerya Respationo; Erniyanti Erniyanti; Fadlan Fadlan; Muhammad Tartib (Annals of Justice and Humanity, 2022)
Purpose: The purpose of this study is to determine the implementation of granting spousal consent in the transfer of land rights from joint property due to unrecorded marriage and to find out the factors that become obstacles and solutions in granting spousal consent in the transfer of land rights from joint property due to unrecorded marriage. Research Methodology: The research method used in this research is normative research method by involving analysis of legal regulations, policies, and legal instruments related to applicable laws and regulations. Results: The result of the research shows that the granting of spousal consent in the transfer of land rights from joint property due to unregistered marriage in Batam City, until now does not have a special regulation, so it still refers to the same provisions as spousal consent to joint property in registered marriages contained in Article 36 of the Marriage Law, and Article 92 KHI and Article 119 KUHPerdata. Limitations: The study is limited to jurisdiction-specific laws and regulations concerning land rights and spousal consent in the context of unregistered marriages. It does not delve into broader family law aspects unrelated to property transfers. Contribution: This research contributes a comprehensive analysis of the legal intricacies involved in transferring land rights from joint property due to unregistered marriages, shedding light on gaps in existing regulations and proposing potential legal remedies. It serves as a valuable resource for legal practitioners, policymakers, and scholars seeking insight into this nuanced area. Practical Implication: The findings of this study have practical implications for legal professionals advising clients on property transactions involving unregistered marriages. Additionally, it provides a basis for legislative reform to address gaps and uncertainties in current legal frameworks.